Emerging Social Actors in Bolivia Between 1990-2005: The Issue of Coca, Water and Gas (Global Journal of Human-Social Science, 2023)
In this essay, the main social actors that emerged in Bolivia in the period between 1990 and 2005 will be analyzed. To do this, first, the concept of social actors briefly developed from the definition of relevant authors of the sciences. social. Subsequently, the emergence and importance of the three coordinators that are constituted from the most important conflicts of those years will be described, that of the coca growers against the prohibition of coca cultivation, and those of the water and gas coordinators against the privatization of both resources. Then, some assessments will be made about the ways in which these particular demands of the three social actors converge, generating what Laclau (2005) calls popular demands. Finally, it will be concluded that the particularities and importance of these experiences, both separately and together, are very useful for the study and practice of politics as an engine of social transformation.
Keywords: social groups - bolivia - state – democracy